2000
DOI: 10.1002/(sici)1098-1004(200005)15:5<483::aid-humu19>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Mutation analysis in 36 unrelated Spanish subjects with familial hypercholesterolemia: Identification of 3 novel mutations in the LDL receptor gene

Abstract: We used the single strand conformation polymorphism (SSCP) method to investigate 36 apparently unrelated Spanish patients with familial hypercholesterolemia (FH) for mutations in the promoter region and the 18 exons and their flanking intron sequences of the low density lipoprotein receptor (LDLR) gene. Nineteen aberrant SSCP patterns were found, and the underlying mutations were characterized by DNA sequencing. In addition, we tested all patients for the presence of mutations in the gene coding for apolipopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
18
3
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 20 publications
6
18
3
2
Order By: Relevance
“…Both variants have been reported as disease-causing in HGMD. 38,49 Here, we only identified both variants in the index patients of family 7080 and 8985 and not in the two other affected family members. Both index patients have markedly elevated LDLC levels of 310 and 204 mg/dl, respectively.…”
Section: Ldlr Gene Variantsmentioning
confidence: 82%
“…Both variants have been reported as disease-causing in HGMD. 38,49 Here, we only identified both variants in the index patients of family 7080 and 8985 and not in the two other affected family members. Both index patients have markedly elevated LDLC levels of 310 and 204 mg/dl, respectively.…”
Section: Ldlr Gene Variantsmentioning
confidence: 82%
“…Interestingly only four mutations were found in common with the Spanish FH population, namely M-21L [15], S156L [16], D200G [17], and G322S [18] and this last one also with the Brazilian population [19]. From the available literature it seems that not enough FH patients have been studied in these three countries for results in the populations to be compared.…”
Section: Discussionmentioning
confidence: 97%
“…Previous literature (Jensen et al 1996;Heath et al 2000;Mozas et al 2000) had indicated significant linkage disequilibrium with mutation T705I in exon 15. Our direct tests for T705I in subjects positive for 1061-8T→C were all positive, whereas other subjects tested were negative.…”
Section: Specific Comments On Sequence Variants Identified From Cohormentioning
confidence: 91%
“…Sequencing of exon 15 was undertaken for samples positive for 1061-8T→C in exon 8 since it was suspected (Jensen et al 1996;Heath et al 2000;Mozas et al 2000) that mutation T705I and i7-8 would co-occur. Residual genomic DNA in the respective meltMADGE exon 8 PCR products was used as template and primers both for exon 15 PCR and subsequent sequencing were 5Ј-AGGCGCACACCTATGAGAAG-3Ј (sense) and 5Ј-GTGAGGACGACACCTGGACT-3Ј (antisense).…”
Section: Generation Of Artificial Positive Controls For Ldlr Ampliconsmentioning
confidence: 99%